The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1260/0144-5987.30.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Hydrolysis of Corn Stover for Improved Ethanol Production

Abstract: Response surface methodology (RSM) was used to optimize the enzymatic hydrolysis of corn stover (CS), an abundant agricultural residue in the USA. A five-level, three-variable central composite design (CCD) was employed in a total of 20 experiments to model and evaluate the impact of pH (4.1-6.0), solids loadings (6.6-23.4%), and enzyme loadings (6.6−23.4 FPU g −1 DM) on glucose yield from thermo-mechanically extruded CS. The extruded CS was first hydrolyzed with the crude cellulase of Penicillium pinophilum A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Table 2 presents the results of different S. cerevisiae fermentations using the same microbial strain, pretreatment, and/or feedstock as in the present work. Zambare et al (2011 and used S. cerevisiae ATCC 24860 and an SHF configuration for ethanol production from Spartina pectinata and corn stover, respectively [55,56]. Both studies reported lower ethanol concentrations and productivities than the present work.…”
Section: Bioreactor Assaysmentioning
confidence: 57%
“…Table 2 presents the results of different S. cerevisiae fermentations using the same microbial strain, pretreatment, and/or feedstock as in the present work. Zambare et al (2011 and used S. cerevisiae ATCC 24860 and an SHF configuration for ethanol production from Spartina pectinata and corn stover, respectively [55,56]. Both studies reported lower ethanol concentrations and productivities than the present work.…”
Section: Bioreactor Assaysmentioning
confidence: 57%
“…Corn stover, including the leaves, husk, and stalks, comprises up to half of the crop's yield and is one of the most abundant agriculture residues in United States . Raw corn stover consists of about 49.6% glucan, 25.1% xylan, and 23.7% lignin, and has been studied for its potential contribution to the production of biofuels, and biobased lactic acid . Sorghum has been recommended as a feedstock for biofuel production, and of potential crops, has the highest water use efficiency and a high tolerance to low soil fertility .…”
Section: Introductionmentioning
confidence: 99%
“…Various hydrolytic enzymes are required to achieve efficient biodegradation of lignocellulosic biomass because of its inherent complexity and heterogeneity ( Zambare and Christopher, 2012 ). T. reesei was developed to enhance cellulase production by overexpressing CBHII.…”
Section: Resultsmentioning
confidence: 99%